Pengaruh Penempatan Terhadap Kinerja Pegawai Pada Kantor Pengadilan Negeri Tanah Grogot Kelas II - Syifi Fauziyah; Erni Susanti; Indah Indah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The purpose of this research is to determine the effect of Placement (X) consisting of Education (X1), Work Knowledge (X2), Work Skills (X3), and Work Experience (X4) on the Employee Performance variable (Y) at the Tanah Grogot District Court Office Class II. The sample in this study were employees at the Class II Tanah Grogot District Court Office using a saturated sampling technique and the number of samples obtained was 34 people. Employees as samples in this study were given a questionnaire consisting of 13 statements. The responses to this questionnaire were tested for validity and reliability before carrying out multiple linear regression analysis using the SPSS application. The results of testing the instrument, namely the questionnaire, show that the 13 statement items are valid because rcount > rtable is (0.339). Apart from that, all statements are reliable because Cronbach's alpha (α) > 0.60 (0.905 > 0.60). The regression equation obtained is Y = 1.460 – 0.133 X1 + 0.398 X2 – 0.133 X3 + 0.551 X4. The multiple correlation coefficient (R) value is 0.762, which means a strong correlation between the variables Education (X1), Work Knowledge (X2), Work Skills (X3), and Work Experience (X4) on the Employee Performance variable (Y). The coefficient of determination (Adjusted R2) value of 0.522 or 52.2% shows the large contribution of the Placement variable (X) which consists of Education (X1), Work Knowledge (X2), Work Skills (X3), and Work Experience (X4) to the variable Employee Performance (Y) was 52.2%, while the rest was explained by other variables not included in this research amounting to (100-52.2) % = 47.8%. Simultaneous testing (F test) shows that Fcount > Ftable (10.012 > 2.70) or p-value (Fcount) > α (0.000 < 0.05), meaning that H0 is rejected and Ha is accepted so it can be concluded that there is an influence between the placement variables which consists of Education (X1), Work Knowledge (X2), Work Skills (X3), and Work Experience (X4) on the Employee Performance variable (Y) at the Class II Tanah Grogot District Court Office. Partial testing (t test) shows that the value of tcount > ttable on Job Knowledge (X2), namely 3.198 > 1.699 and Work Experience (X4), namely 3.138 > 1.699, there is a significant influence on Employee Performance (Y) at the Class II Tanah Grogot District Court Office, which means H0 is rejected and Ha is accepted, while the value of tcount < ttable for Education (X1) and Work Skills (X3) has no significant influence on Employee Performance (Y) in the Clerk's Office at the Class II Tanah Grogot District Court Office. In the Placement variable (X) which consists of the four variables studied, the dominant variable is Job Knowledge (X2) as evidenced by the highest t-count value of 3.198 and the lowest significant value of 0.003.